Metallized adhesive tape in lettuce production in an aquaponic system (Research, Society and Development, 2023)
Aquaponics is a production system in which the integration between fish, bacteria and plants occurs, and the vegetal development is directly related to parameters such as temperature and luminosity. The use of metalized adhesive tape is a common practice in vegetal production, but its efficiency in aquaponics is still unknown. In this sense, the present study evaluated the use of metallized tape covering the floating trays in aquaponic systems and its effect on lettuce performance (Lactuca sativa, var. Marisa) integrated with Oreochromis niloticus tilapia juveniles. Each system had a fish tank, three plastic boxes forming the hydroponic bench, as well as a mechanical and biological filtration system. Although the treatment with metallized tape presented the highest luminance in comparison to the treatment without tape, the latter showed the best phytotechnical results for lettuce. The tilapia zootechnical performance was similar between treatments. Under the experimental conditions evaluated despite the increase on luminance, the metallized tape showed no improvement on the plant performance.